Understanding and targeting MET signaling in solid tumors - are We there yet? - Ariyawutyakorn W. (2017)
© Ivyspring International Publisher. The MET signaling pathway plays an important role in normal physiology and its deregulation has proved critical for development of numerous solid tumors. Different technologies have been used to investigate the genomic and proteomic status of MET in cancer patients and its association with disease prognosis. Moreover, with the development of targeted therapeutic drugs, there is an urgent need to identify potential biomarkers for selection of patients who are more likely to derive benefit from these agents. Unfortunately, the variety of technical platforms and analysis criteria for diagnosis has brought confusion to the field and a lack of agreement in the evaluation of MET status as a prognostic or predictive marker for targeted therapy agents. We review the molecular mechanisms involved in the deregulation of the MET signaling pathway in solid tumors, the different technologies used for diagnosis, and the main factors that affect the outcome, emphasizing the urge for completing analytical and clinical validation of these tests. We also review the current clinical studies with MET targeted agents, which mostly focus on lung cancer.